Development of Biodegradable Films Loaded with Phages with Antilisterial Properties - Lopez de Dicastillo-Bergamo, A (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The inhibitory and bactericidal capacity of Listex P100 bacteriophage has been studied against different concentrations of Listeria monocytogenes in stationary and exponential phases. Three different matrices were employed to developed films incorporating Listex P100: (1) sodium caseinate, (2) sodium alginate mixed with gelatin, and (3) polyvinyl alcohol (PVOH). All the films were successfully developed by casting at room temperature. These active biodegradable films were optical, structural, and thermally characterized, and their antimicrobial capacities against L. monocytogenes were studied. The incorporation of phages did not affect the morphology, colour, opacity, and thermal stability of polymers. The antimicrobial analysis revealed the bacteriophage presented a high antimicrobial capacity against L. monocytogenes in the stationary phase (4.40 and 6.19 log reduction values or bactericide effect depending on the initial inoculum of the pathogen). Developed films showed antimicrobial capacity close to 1 log after 24 h of incubation at 30◦C. The effectiveness of PVOH films was greater under refrigeration conditions, reaching 2 log reduction after eight days of incubation. The use of these films as a coating in a food or as part of a packaging could improve food safety against the growth of pathogenic microorganisms such as Listeria monocytogenes. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.